Kodifikasi Hukum Keluarga Islam di Negara Muslim: Dinamika Reformasi, Metode Pembaruan, dan Tantangan Implementasi - Anna Muwaffika; Ibnu Radwan Turnip; Rahmad Efendi; Taufik (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Islamic family law reform is a response to the evolving social, cultural, and political dynamics in Muslim countries, particularly post-colonial countries. In many countries, including Morocco, family law is influenced not only by Sharia but also by Western legal systems and local traditions. This situation has prompted states to reform family law through codification, reinterpretation of religious texts, and adaptation of laws to align with the needs of modern society, particularly in efforts to protect women's rights and achieve gender equality. This study aims to analyze the forms, methods, and factors influencing Islamic family law reform. The methodology used is normative legal research with statutory, historical, and conceptual approaches. Data were obtained through a literature review of laws and regulations, Islamic legal doctrine, academic literature, and relevant scientific works. The results indicate that Islamic family law reform is carried out through various methods, such as takhayyur, talfiq, ijtihad, legal codification, and procedural adaptation through the modern judicial system. These reforms reflect efforts to adapt sharia to social change while still considering the values of justice, welfare, and equality, so that Islamic family law can function effectively in contemporary society